Peningkatan Kapasitas Guru TK ABA se-Sedayu dalam Upaya Perubahan Perilaku Murid Melawan Covid-19 - Iman Permana; Martinus Sardi; Winny Setyonugroho; Hanifah Hanifah (Jurnal Pengabdian Pada Masyarakat, 2021)
CAPACITY BUILDING FOR TK ABA TEACHERS IN SEDAYU AS AN EFFORT TO CHANGE STUDENT BEHAVIOR AGAINST COVID-19. The Covid-19 pandemic has occurred for more than a year, started in March 2020. Many daily activities have become limited. It is difficult to predict whether the conditions caused by the Covid-19 pandemic will improve at this time. All levels of society need to adopt new habits at this time. This new habitual habit in health education activities will be more meaningful if instilled from an early age. TK ABA teachers have great potential to help instill new habits for their students from an early age. The extensive network of TK ABA’s further strengthens this potential. Therefore, developing a teacher capacity-building model is one of the keys to changing people's behavior against the Covid-19 pandemic. The community service activities began with extracting information and perceptions of TK ABA teachers about the Covid-19 pandemic through Focus Group Discussions (FGD). The next activity is the delivery of educational materials and training on healthy living. The pre-test and post-test were used to measure the achievement of the material presented. The results showed an increase in the knowledge of TK ABA teachers after receiving materials and training. Participants were very cooperative and enthusiastic in participating in a series of community service activities.